PENYULUHAN EFEKTIVITAS DAUN SIRSAK TERHADAP PENGOBATAN HIPERTENSI PADA IBU HAMIL DI DESA BATU GANA KECAMATAN PADANG BOLAK JULU KABUPATEN PADANG LAWAS UTARA: EFEKTIVITAS DAUN SIESAK - Harahap, Riska Yanti; Nainggolan, Ramadhani (JURNAL SUAKA INSAN MENGABDI (JSIM), 2024)
Hypertension is a non-communicable disease which is often referred to as a "silent killer" which can be defined as a condition where the blood vessels have high blood pressure (systolic blood pressure > 140. Soursop leaves are often used as an alternative treatment for hypertension. The content of soursop leaves which is thought to be able to lower blood pressure is potassium ions. Objective: to determine the effectiveness of soursop leaves (Annona muricata Linn) in reducing blood pressure in hypertension. Method: Using literature studies from both national and international journals by summarizing the discussion topics and comparing the results presented in each article. Results: Potassium ions have several mechanisms in lowering blood pressure, namely weakening myocardial contractions, increasing sodium excretion from the body, inhibiting renin excretion, causing vasodilation, and inhibiting endogenous vasoconstriction. High potassium levels can increase sodium excretion , so it can reduce blood volume and blood pressure. Flavonoids work as ACE inhibitors which will inhibit the change of AI to AII thereby reducing the secretion of antidiuretic hormone (ADH) which causes the amount of urine secretion to increase and a lot of salt (NaCl) to be excreted, ultimately resulting in a decrease in blood pressure. Vitamin C also plays a role in lowering blood pressure, because it can modulate the release of nitric oxide. Conclusion: giving soursop leaves can reduce blood pressure levels in hypertension, especially pregnant women. Based on these conclusions, it is necessary to provide education about the effectiveness of soursop leaves in treating hypertension in all pregnant women.